Programa Bolsa Família, representações sociais e charges na internet - Vieira, Daiana Schneider (2017)
This Master's thesis aimed to identify and problematize the knowledge built around the Bolsa Família Program (BFP). For that, we elaborated two papers: "Social Representations in editorial cartoons about 'Bolsa Família': what do the beneficiaries tell us about it?", and "Let's talk about Bolsa Família? The dialogue among teaching, research and extension". In the first paper, we aimed to analyze how female beneficiaries represent the BFP and if there may be identifications and significations of their experiences with the social program. The empirical research was conducted through epistemology circles involving nine female beneficiaries of BFP, linked to a CRAS (Reference Center for Social Assistance) from a city in RS. The analysis is based on the epistemological perspective of Critical Social Psychology and the Theory of Social Representations, and it also uses the theoretical concepts of ideology, in its critical sense, and hyper-representations. The study pointed that in most situations there was no signification and identification between the experiences of these women and the contents of the cartoons, which presented negative ideological hyper-representations about the BFP beneficiaries. In the situations in which there was some identification, it was because the cartoons referred to situations that were familiar to them through the mass media, but distant from them in time or space. In the second paper, we brought an experience report about the extension project "Empowering affectivity and criticism through art and dialogicality: the invisible lives or invisibilities of the health object", to which this thesis is linked. The project was carried out during 2015 and 2016, simultaneously to the period of the master's degree. The report was divided into three parts: (a) Studying about Bolsa Família and cinema, (b) Rehearsing for the documentary, and c) Presenting the extension activity. We concluded that the activities related to the extension project enabled important experiences that contributed to improve the research topic. We highlight the importance of interdisciplinary work and the use of documentary films to work and (re)think social issues, such as the Bolsa Família Program, under the light of Critical Social Psychology and the Theory of Social Representations.